The use of ‘abundant life’ in John 10:10 and its interpretation among some Yoruba prosperity gospel preachers - Mbamalu, Abiola I. (University of KwaZulu-Natal, 2010)
This is a case study that focuses on how John 10:10, with its mention of abundant life, has been interpreted by some Yoruba preachers of the ‘prosperity gospel’ in the course of preaching and teaching. The quotation below is one way in which John 10:10 has been understood: No one has an inheritance in a family to which he does not belong. In the same way being born again is a prerequisite for you to be an inheritor of the rich heritage made available by covenant through the shed blood of Jesus. It is our heritage to be fruitful, prosperous, healthy and to enjoy long life among other things because Jesus came to give the believer an abundantly good life (Jn. 10:10).1 The underlying presupposition that has facilitated this understanding is usually left undisclosed; rather all the congregation hears is that “this is the word of God”. The manner in which this understanding is attained and grounded is the concern of this study. Is this type of reading responsible or legitimate? Does it commit God to do what the preacher says God would do? Does it adequately reflect the message of Jesus as portrayed in the fourth gospel? To what extent is the interpretation in continuity or discontinuity with past understanding of other readers of the same text? From what vantage point is this type of reading taking place? These are the issues that this study grapples with. The hypothesis of this study is that the context of the Yoruba prosperity preacher has a great influence on his/her understanding and interpretation of this passage of scripture. In terms of the social location of the researcher, she is a Yoruba who has lived in the Yoruba context since birth until about a decade ago to engage in further studies. She got exposed to Campus Christianity in the early 80s and became ‘born-again’ then. She is a member of one of the Classical Pentecostal churches in Nigeria.
free